2019
DOI: 10.1038/s42003-019-0434-2
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase PHR promotes directional regrowth of spinal zebrafish axons

Abstract: To reconnect with their synaptic targets, severed axons need to regrow robustly and directionally along the pre-lesional trajectory. While mechanisms directing axonal regrowth are poorly understood, several proteins direct developmental axon outgrowth, including the ubiquitin ligase PHR (Mycbp2). Invertebrate PHR also limits regrowth of injured axons, whereas its role in vertebrate axonal regrowth remains elusive. Here we took advantage of the high regrowth capacity of spinal zebrafish axons and observed robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 94 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…Consequently, it was essential to define the particular time course of the complete regeneration event of M-cell in our experimental setting. Wallerian degeneration ( Bremer et al, 2019 ; Hecker et al, 2020 ) of M-cell i.e. fragmentation and initiation of cell-debris clearance together with regeneration were observed at 8–9 h and 12 h of post-transection, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it was essential to define the particular time course of the complete regeneration event of M-cell in our experimental setting. Wallerian degeneration ( Bremer et al, 2019 ; Hecker et al, 2020 ) of M-cell i.e. fragmentation and initiation of cell-debris clearance together with regeneration were observed at 8–9 h and 12 h of post-transection, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…And in this way, we had the only variable to observe and that was the treatment of different small molecules. Several studies have been performed which elucidate the M-cell regeneration processes ( Xu et al, 2017 ; Hu et al, 2018 ; Bremer et al, 2019 ; Hecker et al, 2020 ). All these studies have supported the dependency of time-course upon the type of injury together with the stage of the larvae and ultimately upon the operator.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, experiments in axotomized Mauthner axons revealed that axons cross the lesion site by first initiating multidirectional sprouting and then correcting their route in a ubiquitin ligase Pam/Highwire/Rpm-1 (PHR)-dependent manner. This process was largely dependent on the tight regulation of actin polymerization by cytoplasmic FMR1 interacting protein 2 (Cyfip2) and c-Jun N-terminal kinase (JNK) signaling pathways [125], implicating growth cone extension for axon regeneration. While knowledge on intrinsic pro-regenerative factors in spinal-projecting neurons is still limited, previous studies on the optic nerve, which likewise robustly regenerates in zebrafish, have resulted in additional insights and are reviewed in detail elsewhere [52].…”
Section: Intrinsic Regenerative Capacitymentioning
confidence: 99%
“…1a, b). Following distal injury (1599 ± 31 μm; N = 28), the severed caudal part of the M-axon always (14 of 14 cases) degenerated within 24 h through Wallerian degeneration 19,41 . The rostral part of the M-axon that was still in contact with its soma often withdrew a few micrometers from the injury site but always survived.…”
Section: Proximity Of Injury Site To the Soma Determines Regenerationmentioning
confidence: 99%